The Relationship Between Family Support and Anxiety Levels in Preoperative Patients with Reponible Hernia - Dede Andri Apriansyah; Hadi Abdillah; Ernawati Hamidah; Hendri Hadiyanto (Jurnal Keperawatan Priority, 2026)
Patients undergoing surgery often experience anxiety due to concerns about surgical outcomes, pain, and potential complications. Family support plays a vital role in helping patients cope with anxiety before surgery. This study aimed to determine the relationship between family support and anxiety levels among preoperative hernia reponibel patients in Nyi Ageng Serang Room 1 at RSUD Sekarwangi. A quantitative cross-sectional design was employed. The sample consisted of 32 preoperative patients with reducible hernia, representing the total population treated in the study setting during the data collection period. Patients selected using a total sampling technique. The research instruments used were the Multidimensional Scale of Perceived Social Support (MSPSS) to assess family support and the Hamilton Anxiety Rating Scale (HARS) to measure anxiety levels. Data were analyzed using the Chi-Square test with a significance level of p < 0.05. The results revealed a significant relationship between family support and patients’ anxiety levels (p = 0.000). Patients who received strong family support predominantly experienced mild anxiety (87.5%), while those with low family support tended to experience moderate to severe anxiety. These findings indicate that greater family support is associated with lower anxiety levels among preoperative patients. This study contributes evidence that family support is a significant determinant of preoperative anxiety among patients with reducible hernia in a regional hospital setting. The findings enrich nursing science by highlighting the importance of family-centered care as a contextual psychological support strategy in preoperative management, particularly in non-tertiary hospitals.